78.7k views
5 votes
PRECALCULUS please help​

PRECALCULUS please help​-example-1

1 Answer

6 votes

Answer:


( f - g)(x) = (2x - √(x) + 14 )/(3x)

Explanation:


f(x) = (2x + 6)/(3x) \\ \\ g(x) = ( √(x) - 8)/(3x)

To find ( f - g)(x) , subtract g(x) from f(x)

That's


( f - g)(x) = (2x + 6)/(3x) - ( √(x) - 8)/(3x)

Since they have a common denominator that's 3x we can subtract them directly

That's


(2x + 6)/(3x) - ( √(x) - 8)/(3x) = (2x + 6 - ( √(x) - 8) )/(3x) \\ = (2x + 6 - √(x) + 8 )/(3x) \\ = (2x - √(x) + 6 + 8 )/(3x)

We have the final answer as


( f - g)(x) = (2x - √(x) + 14 )/(3x)

Hope this helps you

User Keyadun
by
6.0k points